Role of doping-induced photochemical and microstructural properties in the photocatalytic activity of InVO4 for splitting of water - Rakesh, K.; Khaire, S.; Bhange, Deu S.; Dhanasekaran, P.; Deshpande, Suvarna S.; Awate, S. V.; Gupta, N. M. (Journal of Materials Science, 2011)
We report in this paper on microstructural, optical and photocatalytic properties of single-phase indium orthovanadates, as a function of doping at lattice sites. The UV-visible spectra of these samples exhibited intense UV-region bands at 250 and 350 nm, besides broad absorption band in visible region (350-700 nm). The wavelength at absorption edge and the intensity of visible absorption showed considerable increase on doping of an impurity, particularly at V or O lattice sites. Also, the samples gave rise to blue-green photoluminescence emission, with overriding bands at ca. 420, 450, 460 and 485 nm, on excitation at 240-420 nm wavelengths. The intensity of these fluorescence bands varied with excitation wavelength and impurity content of a sample. In deviation with several earlier studies, only oxygen and no hydrogen were produced during photocatalytic splitting of water, in the experiments conducted under visible light (> 395 nm) and at a pH of similar to 6.5. The O-2 yield depended on the dispersed metal co-catalyst, impurity content and the addition of methanol as sacrificial reagent. On the other hand, small quantities of hydrogen and no oxygen were evolved on UV-irradiation of pure water using metal/InVO4. These results are ascribed to flat band potentials and the doping-induced inter-band donor and acceptor charge trapping states of InVO4, the presence of which is revealed by XRD, luminescence and XPS studies. Our study also confirms that the onset of absorption edge may not necessarily correspond to band-to-band energy gap of a semiconducting material. This accounts for some anomalous band gap energies reported earlier for InVO4.

Role of micro-structure and interfacial properties in the higher photocatalytic activity of TiO2-supported nanogold for methanol-assisted visible-light-induced splitting of water - Awate, S. V.; Deshpande, Suvarna S.; Rakesh, K.; Dhanasekaran, P.; Gupta, N. M. (Physical Chemistry Chemical Physics, 2011)
This paper deals with the textural, microstructural and interfacial properties of Au/TiO2 nanocomposites, in relation to their photocatalytic activity for splitting of water. TiO2 samples of two different morphologies were employed for dispersing different cocatalysts, such as: Au, Pt, Ag or Cu, for the sake of comparison. The samples were characterized using powder XRD, XPS, UV-visible, thermoluminescence, SEM, HRTEM and SAED techniques. Compared to other metal/TiO2 photocatalysts, Au/TiO2 with an optimum gold loading of 1 wt% was found to exhibit considerably higher activity for visible light induced production of H-2 from splitting water in the presence of methanol. Further, the sol-gel prepared TiO2 (s.TiO2), having spherical grains of 10-15 nm size, displayed better photoactivity than a Degussa P25 catalyst. The electron microscopy investigations on s.TiO2 revealed significant heterogeneity in grain morphology of individual TiO2 particles, exposure of the lattice planes, metal dispersion, and the interfacial metal/TiO2 contacts. The gold particles were found to be in a better dispersed state. O-2 TPD experiments revealed that the gold nanoparticles and Au/TiO2 interfaces may serve as distinct binding sites for adsorbate molecules. At the same time, our thermoluminescence measurements provide an insight into Au-induced new defect states that may facilitate the semiconductor-to-metal charge transfer transition. In conclusion, the superior photocatalytic activity of Au/TiO2 may relate to the grain morphology of TiO2, dispersion of gold particles, and the peculiar architecture of metal/oxide heterojunctions; giving rise in turn to augmented adsorption of reactant molecules and their interaction with the photo-generated e(-)/h(+) pair. The role played by methanol as a sacrificial reagent in photocatalytic splitting of water is discussed.